Optimizing heating efficiency: The role of sunspace geometry - Erdem, Serkan; Onan, Cenk (ELSEVIER SCIENCE SA, 2025)
Solar energy stands out among renewable energy sources due to its efficiency and ease of application, making it a preferred option. It can be utilized through both active and passive systems, significantly reducing heating costs. Sunspaces, a type of passive heating system, not only provide additional usable spaces but also decrease the heating load of buildings. However, studies and market applications indicate that the roof slopes of sunspaces are generally not significantly varied. Additionally, the depth of the sunspace is often determined based on the area of use, which can limit the full utilization of its energy potential. In this study, the impact of sunspace geometry on energy savings was investigated. A scaled model of a detached house with a sunspace was created in Istanbul, and measurements were taken in an open field during winter conditions. Parameters such as indoor and outdoor temperature, humidity, wind speed, and solar energy were examined. This house model was then simulated using TRNSYS software, and the results were compared with experimental data. After confirming that accurate results could be obtained with the computer model, different roof slopes and room depths of the sunspace were simulated. The results determined the effects of roof slope and room depth on energy consumption. Consequently, it became possible to better harness solar energy in sunspaces and reduce heating costs.
Keywords: Passive heating; Solar energy; Sunspace; System analysis; Modeling; THERMAL PERFORMANCE; ATTACHED SUNSPACES; DESIGN; ARCHITECTURE; Construction & Building Technology; Energy & Fuels; Engineering